MATHEMATICAL MODEL OF THE HEART MUSCLE FUNCTIONING LEVEL ESTIMATION BEFORE CORONARY ARTERY BYPASS SURGERY - B. A. Sidorenko; O. A. Semenyuk; M. A. Bugrimova; A. V. Ivanov; M. E. Bilko (Кубанский научный медицинский вестник, 2015)
A total of 100 patients (86% - men, 14% are women), aged 56-69 years, which was later performed coronary artery bypass surgery. The methodology was based on a comprehensive survey assessing the functioning of the heart muscle, the clinical and instrumental parameters, which reflect the state of the cardiovascular system and other vital organs (liver, kidney, pancreas) and blood clotting system. The study developed a mathematical model of the relationship set out indicators ejection fraction of the heart muscle. It is established that as a benchmark, providing a high level of predicting a favorable outcome and the ejection fraction of the myocardium can be considered indicator of the scale of the risk assessment of adverse outcomes (EuroSCORE).